Bronchopulmonary Kaposi's sarcoma. (2015) - Bashar, Nada; Innes, Nicholas; Orrell, Julian
Abstract: Kaposi's sarcoma (KS) is a highly vascular tumour, which was first described by the Hungarian dermatologist Moritz Kaposi Kohn before the discovery of the human immunodeficiency virus (HIV). Historically, KS has been linked to immunosuppression or to elderly male patients, especially in relation to diffuse cutaneous KS. We describe a case of Bronchopulmonary Kaposi's sarcoma in a patient with AIDS who was successfully treated with HAART and Liposomal Doxorubicin chemotherapy.